Eosinophil cationic protein (ECP) correlates with eosinophil cell counts in the induced sputum of elite swimmers. Issue 2 (18th March 2022) - Paciência, Inês; Rocha, Ana Rita; Farraia, Mariana; Sokhatska, Oksana; Delgado, Luís; Couto, Mariana; Moreira, Andre
Abstract: Introduction: Swimming practice has been associated with eosinophilic inflammation, however, the underlying mechanisms are not fully understood. The eosinophil cationic protein (ECP) in induced sputum may be used as a potential biomarker to assess airway eosinophilic inflammation among elite swimmers. The objective of this study is to characterize ECP levels in sputum supernatant in elite swimmers and evaluate ECP as an eosinophilic inflammatory marker. Material and methods: Elite swimmers annually screened in our department (n = 27) were invited to participate in this cross-sectional study. Swimmers who agreed to participate (n = 24, 46% girls) performed lung function and skin-prick tests. Induced sputum was also collected and analyzed for differential cell counts and ECP measurements in sputum supernatant (ImmunoCAP TM 100, ECP, Thermo Fisher Scientific, Uppsala, Sweden). Results: The median ECP level was 15.60 μg/L (6.02–38.75 μg/L) and higher levels were found among boys (27.90 (11.20–46.30) μg/L vs 6.65 (2.82–22.80) μg/L, P = .02). In addition, ECP levels in the sputum supernatant were positively correlated with eosinophil cell counts in the induced sputum ( r = 0.583, P = .08). Conclusions: ECP levels correlated positively with eosinophil counts in the induced sputum in elite swimmers. The measurement of ECP in sputum supernatant may be a useful marker to assess and manage eosinophilic inflammatory changes in the airways of elite swimmers.